Working knowledge : employee innovation and the rise of corporate intellectual property, 1800-1930 - Fisk, Catherine L., 1961- (Studies in legal history., 2009)
In most sectors of today's economy, it is a foundational and widely accepted truth that businesses retain legal ownership of employee-generated intellectual property. That was not the case in the 19th century, however, when workplace knowledge and technical skill were considered the property of skilled workers. Fisk chronicles the legal and social transformations that led to the transfer of ownership of employee innovation from labor to management and argues that this deeply contested development was won at the expense of workers' entrepreneurial independence and ultimately economic democracy.